Kelayakan Finansial Pembangunan Batching Plant PT. Waskita Beton Precast,Tbk Provinsi Sulawesi Utara - Desi Yasri; Hendra Widodo; Yulia Setiani (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2020)
The Batching Plant establishment project of PT. Waskita Beton Precast, Tbk is aimed to meet the needs of its own ready mix concrete to develop 2 km of Manado-Bitung Toll Road. The establishment of this batching plant was caused by the worry that demand for concrete need with a volume of 73,000 m³ was not fulfilled which has been planned for the period of 33 months (June 2016 to December 2018). This temporary project evaluation is needed for assessing the time of return on investment capital and the achievement evaluation using investment criteria. Investment evaluation used 3 (three) analytical techniques commonly used in Benefit-Cost Analysis (BCA), namely Net Present Value (NPV), Internal Rate of Return (IRR) and Cost-Benefit Ratio (BCR). The investment evaluation results showed that the decision criteria with NPV of Rp. 3,721,209,360.08, where NPV> 0, IRR of 107.82%, gave the value of IRR > 4.92% and with BCR of 1.054, gave the value of BCR> 1. All calculation results showed the value of the criteria that the Batching Plant Project of PT. Waskita Beton Precast, Tbk is eligible and makes a profit.